Một số vấn đề cơ bản của hệ điều hành thời gian thực - Tân, Phan Minh (Journal of Computer Science and Cybernetics, 2016)
The paper deals with the design and functions of real – time operating systems. It gives an overlook for multitasking, priority and enterrupt handling as well as basic requirements and structure of an real – time operating systems. Some examples are also given for illustration of the principles.